1998
DOI: 10.1203/00006450-199811000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Human Infant Cerebral Arteries to Sympathetic Nerve Stimulation and Vasoactive Agents

Abstract: Responses of segments of basilar and middle cerebral arteries of eight human infants to activation of perivascular nerves and to vasoactive drugs were studied using a resistance artery myograph. The infants ages ranged from 23 wk of gestation to 34 postnatal days. Neurogenic vasoconstriction occurred in all segments and at 8 Hz was 12.7 +/- 3.5% (11%) of tissue maximum and was blocked by phentolamine (10(-6) M). There was no evidence of a neurogenic dilator response. Catecholamine histofluorescence was seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…These results also imply that such cells were involved in the regulatory processes of cerebral blood flow. In mammals, the large cerebral arteries, including the basilar artery, are usually the major contributors to the blood flow in the mammalian brain (Bevan et al 1998). This may be of particular importance following regression of the internal carotid artery in mature capybara (Reckziegel et al 2001).…”
Section: Et-1mentioning
confidence: 99%
“…These results also imply that such cells were involved in the regulatory processes of cerebral blood flow. In mammals, the large cerebral arteries, including the basilar artery, are usually the major contributors to the blood flow in the mammalian brain (Bevan et al 1998). This may be of particular importance following regression of the internal carotid artery in mature capybara (Reckziegel et al 2001).…”
Section: Et-1mentioning
confidence: 99%
“…Studies of cerebral arteries, including those in humans, have found that Ang II produces vasoconstriction (Whalley et al, 1985, 1987; Toda et al, 1990; Bevan et al, 1998; Stenman and Edvinsson, 2004; Miller et al, 2005; Vincent et al, 2005; Faraci et al, 2006; De Silva et al, 2009; Amberg et al, 2010; Ahnstedt et al, 2011). Both genetic and pharmacological approaches have established that Ang II induces constriction of cerebral arteries via activation of AT1 receptors (Naveri et al, 1994; Stenman and Edvinsson, 2004; Faraci et al, 2006).…”
Section: Effects Of Ang II On Cerebrovascular Functionmentioning
confidence: 99%
“…Since premature [5] and sick infants [6] have increased blood-brain barrier permeability, direct cerebrovascular as well as cerebral effects of antihypotensive therapy seem possible [7]. Contribution of adrenergic mechanisms to cerebrovascular regulation may be relatively unique to the developing brain [8], [9]. Thus, understanding how commonly used vasopressor-inotropes affect cerebrovascular mechanisms is of major clinical relevance in newborn infants.…”
Section: Introductionmentioning
confidence: 99%